(untitled) (ADMPG Journal, 2021)
In Brazil there are 6.4 million establishments, of which 99% are Micro and Small Enterprises (SMEs), representing just over 52% of all formal jobs in Brazil. However, when it comes to exports, there are just over nine thousand exporting companies, according to data from Sebrae, 2018. In terms of average values, the participation becomes insignificant. Even though the benefits of this practice are known, their participation in exports is considered to be insignificant. SMEs are an important part of the generation of jobs and income in the country, although they face difficulties. Thus, this research aims to identify the challenges of the first export for micro and small entrepreneurs. A qualitative research was carried out with companies participating in the export qualification program (PEIEX) that was carried out by the Fundação Escola de Comércio Álvares Penteado (FECAP) between the years 2018 and 2020. Through semi-structured interviews analyzed by the technique of Content Analysis, it was observed seven challenges categorized in this study; highlighted, are the management, procedural and marketing challenges. It is concluded that it is necessary to pay attention to the need for training, promotion and support programs for SMEs, as well as the practice of new technologies that facilitate and encourage these companies to export.